D. R. Shackleton Bailey (ed.), Cicero XVa, Philippics 1-6 (Revised by John T. Ramsey and Gesine Manuwald). Loeb Classical Library 189, Cambridge, Mass. - London: Harvard University Press, 2009, pp. lxxii + 321, ISBN 9780674996342 - Josiah Osgood (Exemplaria Classica, 2012)
D. R. Shackleton Bailey (ed.), Cicero XVb, Philippics 7-14 (Revised by John T. Ramsey and Gesine Manuwald). Loeb Classical Library 507, Cambridge, Mass. - London:  Harvard University Press, 2009, pp. ix + 365, ISBN 9780674996359